Management of Suspected Pemphigus Vulgaris in Elderly Patient with Chronic Diseases - Ayu M. Prihanti; Muhammad Jusri (Faculty of Dentistry, Universitas Indonesia, 2013)
<!--[if gte mso 9]> 72 1024x768 <![endif]--> <p class="MsoNormal" style="text-align: justify; mso-pagination: none; tab-stops: 28.0pt 56.0pt 84.0pt 112.0pt 140.0pt 168.0pt 196.0pt 224.0pt 252.0pt 280.0pt 308.0pt 336.0pt; mso-layout-grid-align: none; text-autospace: none;">Pemphigus vulgaris (PV) is a group of vesicobullous disease affecting skin and mucous membranes. PV is associated with autoimmune diseases, characterized by binding of IgG autoantibodies to desmoglein 3. PV lesion is a thin-walled bulla arising on the skin or mucosa. Oral mucous bulla are fragile and easily breakdown, forming irreguler ulcers. There are several factors that trigger PV, including genetic factors, age, drugs and food. This paper aimed to report treatment of suspected pemphigus vulgaris in elderly patient with history of chronic diseases. A 75-year-old woman with 2 months history of bulla formation on skin and history of persistent oral ulceration. Ulcers were covered with fibrin and erosive erythematous on labial, buccal and gingival mucosa. History of hypertension, diabetes mellitus and hepatitis was revealed. Routine complete blood count showed thrombocytopenia. Diagnosis was confirmed by anamnesis, clinical examination and complete blood investigation. PV should be distinguished from other vesicobullous disease. Systemic corticosteroid was given concurrently with hepato-protector, mouthwash, supportive therapy and topical lip cream. Bulla on skin and persistent erosive ulcers of the oral mucosa are the manifestations of PV. Elderly patient with history of chronic diseases showed a complex care of PV requiring more intensive and comprehensive treatment. <p class="MsoNormal" style="text-align: justify; mso-pagination: none; tab-stops: 28.0pt 56.0pt 84.0pt 112.0pt 140.0pt 168.0pt 196.0pt 224.0pt 252.0pt 280.0pt 308.0pt 336.0pt; mso-layout-grid-align: none; text-autospace: none;">DOI: 10.14693/jdi.v20i1.129